Historical and Conceptual Underpinnings of Leadership Development Programs: A Quest for Roots - Kent D. Peterson; Fran Wills (Educational Considerations, 1989)
The early prescriptive beliefs about the nature of educational leadership and the professional development that would foster that leadership have changed.